KAJIAN KRITIS FILSAFAT MUTAWAHHID IBNU BAJJAH (TAHAPAN KEDEWASAAN INTELEKTUAL DAN SPIRITUAL MANUSIA) - Hanif, Abdulloh (Jurnal Ilmiah Ilmu Ushuluddin, 2019)
Ibn Bajjah, the first Muslim philosopher in the Western world, who had given a wide influence both to his own Islamic philosophy and many Christian Western thinkers, was a controversial figure. His thoughts besides opening the gate of independent philosophy without the interests of religious polemic also contained puzzles and images of pessimism. His work Tadbir al-Mutawahhid clearly illustrates the impossibility of the formation of al-Farabi's ideal city, also presupposes the impossibility that even divine intellectual perfection cannot change the social conditions of a damaged city. On the other hand, those who have been enlightened with their connection with the Active Intellect (al-qaql al-fa'al) through solitude actually show a passive and pessimistic attitude that looks down on the material world so that the happiness they get is merely personal happiness. This kind of attitude, even though born from universal forms of spirituality, has a resemblance to Schopenhauer's philosophical view which is pessimistic and considers the world and the will of life as obstacles to happiness. But on the other hand, the philosophy of Ibn Bajjah also shows a ladder of psychological maturation, as is the ladder of existence in Kierkegaard's philosophy, where the result is a condition of spirituality that is of the divine value.